Complete interatrial block in a left‐atrial dependent atrioventricular node. (16th July 2021) - Ramos Jiménez, Javier; Marco del Castillo, Álvaro; Rodríguez Muñoz, Daniel; Borrego Bernabé, Luis; Fontenla, Adolfo; López Gil, María
Abstract: Introduction : A middle‐age woman underwent an electrophysiologic study due to recurrent atypical atrial flutter. Methods and Result : Radiofrequency ablation of cavotricuspid isthmus and anterior mitral line was performed. During energy delivery on the anterior left atrial wall, interatrial dissociation and complete block of the sinus impulse to the atrioventricular (AV) node was observed. AV node activation became dependent on a subsidiary left atrial rhythm. Conclusion : Anatomical location of intra and inter‐atrial connections must be taken into account when performing extensive ablation procedures, specially in cases with prior cardiac surgeries.